THE INFLUENCE OF HEALTH EDUCATION ON HEALTH LITERACY, EMOTIONS, AND COPING OF ELEMENTARY SCHOOL STUDENTS: PRE-EXPERIMENTAL DESIGN - Sukaesih, Nunung Siti; Sopiah, Popi; Lindayani, Emi; Pramajati, Hikmat; Hudaya, Ahmad Purnama; Lindasari, Sri Wulan; Faozi, Akhmad (Program Studi Ilmu Keperawatan Universitas Jember, 2026)
ABSTRACT Background: Deaths from non-communicable diseases are increasing in low and middle income countries. Developing school-based health education interventions and programs is one way to improve health literacy skills and abilities from an early age. This program is important for children because increasing literacy skills and abilities in children can predict increasing physical and mental health status and plays an important role in forming healthy habits in children Objectives: The aim of this study was to determine the effect of structured health education on children's health literacy, cognitive, emotional and behavioral, as well as mood and coping. Method: This study was conducted using a pre-experimental design (group intact comparison) with repeated measurements (pre-test and post-test) involving the intervention group and the control group. Elementary school students in grades 4-5 as many as 80 students in the intervention group and 88 students in the control group using several research instruments, namely Health Literacy for Adolescent Tools (HLAT-8), Pediatric Symptom Checklist- 17 (PSC-17), Mood and Feelings Questionnaire -Self report (MFQ-Self). Results: The interaction of health literacy (F(1,166) = 108.3, p < .001, emotional state (F(1,166) = 51.22, p < 0.001), and coping (F(1,166) = 68.71, p < .001). between time and group was significant. This indicates that changes in health literacy, emotioanal state, and coping mechanism scores from pre-test to post-test differet between the intervention and control groups, thus concluding that the intervention was effective in improving health literacy compared to the control group. Conclusion: So it can be concluded that health education using audiovisual media can improve literacy skills in children, improve emotional conditions and reduce the risk of depression in children with good coping. Keywords: Coping; Emotion; Health education; Health literation; Student; Children